The Effect of Chicken Liver and Red Spinach Nuggets on Increasing Hemoglobin Levels in Anemic Adolescent Girls - Ana Mawaddah; Ahmad Sadiq; Nurul Salasa Nilawati; Yulianto; Eliza (Poltekkes Kemenkes Semarang, 2026)
Background: Anemia caused by iron deficiency is a common medical condition experienced by adolescent girls. Providing high-protein and iron-rich foods, such as chicken liver nuggets and red spinach, can serve as an alternative snack for individuals with anemia, given in a portion of 120 grams per day. Purpose: This study aims to determine the effect of administering chicken liver nuggets and red spinach on the increase in hemoglobin levels in anemic adolescent girls at SMA Negeri 19 Palembang. Methods: This study employed a quasi-experimental design using a two-group pretest-posttest approach. The sample consisted of 50 anemic adolescent girls, divided into two groups. The treatment group received chicken liver and red spinach nuggets, while the control group received commercial chicken nuggets, through simple random sampling. The intervention was conducted over 10 days. Data analysis was performed using paired t-tests and independent t-tests to assess significant differences between groups. Results: The mean hemoglobin level in the treatment group before the intervention was 10.98 g/dL, which increased to 12.99 g/dL after the intervention, with an increase of 2 g/dL. Based on the independent t-test, there was a significant difference in the mean hemoglobin level between the treatment and control groups, amounting to 1.23 g/dL and a p-value of 0.000 (<0.05). Conclusion: The administration of chicken liver nuggets and red spinach significantly increases hemoglobin levels in anemic adolescent girls at SMA Negeri 19 Palembang.